World’s Top 2% Scientists List - Agapiou, Athos (My University, 2026)
“World’s Top 2% Scientists List”, Included among the top 2% of highly cited scientists in the world, career-long (Ioannidis, John P.A. (2025), “August 2025 data-update for "Updated science-wide author databases of standardized citation indica-tors"”, Elsevier Data Repository, V8, doi: 10.17632/btchxktzyw.8)
Keywords: World's Top Scientists